Communication as a Catalyst for Motivational Shifts in â€œHow to Make Millions Before Grandma Diesâ€ - Sandra Marissa Sitorus; Rustono Farady Marta; Hana Panggabean; Engliana; Anthony Le Duc (Jurnal Komunikasi Ikatan Sarjana Komunikasi Indonesia, 2025)
The journey of life experienced by an individual, along with the dynamics faced, reflects various motivations influenced by intentions and the environment, shaping individual behavior. This study explores the changes in the motivations of the main character in the film ‘How to Make Millions Before Grandma Dies.’ The main character, influenced by his personal interactions with Amah, alters his motivation from wealth to appreciation of Amah’s legacy of wisdom and relationship. Using the Theory of Reasoned Action (TRA), this research reveals that the motivations shift from externally driven materialistic goals to internally driven emotional goals. Through a qualitative approach employing Todorov's Narrative Analysis Method, the findings demonstrate that interpersonal communication is crucial in transforming motivations, showing how social interactions can influence individual attitudes and behaviors, and highlighting the importance of family values in this transformation process. To conclude, every rational action generates intrinsic and extrinsic drives, regardless of whether the outcome aligns with the original objective. The dynamics and communication involved will lead to self-development. Keywords: Interpersonal Communications; Motivation; Theory of Reasoned Action; Todorov’s Narrative Analysis